2016
DOI: 10.1016/j.mgene.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of Meq oncogene among Indian isolates of Marek's disease herpesvirus

Abstract: Marek's disease (MD), caused by Marek's disease virus (MDV), is a highly contagious neoplastic disease of chicken that can be prevented by vaccination. However, in recent years many cases of vaccine failure have been reported worldwide as chickens develop symptoms of MD in spite of proper vaccination. Distinct polymorphism and point mutations in Meq gene of MDV have been reported to be associated with virulence and oncogenicity. The present study was carried out with the objective to isolate and characterize f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…While meq gene detection indicates the pathogenicity of the virus, the number of repeat sequences of four prolines (PPPP repeats) in the meq gene (overall range 2-8) have been reported to correlate with MDV virulence and oncogenicity [19] with the most pathogenic isolates having the fewest number of repeats [17]. Compared with 30 reference strains, both the isolates have 5 PPPP repeats similar to the six isolates from north India [9] and one each from Hungary and South India indicating the virulence potential. The isolates in cluster II have 2-4 PPPP repeats while the isolates in cluster III have PPPP repeats ranges from 4 to 7 probably indicating the level of pathogenic potential of the isolates in each clusters.…”
Section: Phylogenetic Analysis and Determination For Virulencementioning
confidence: 98%
“…While meq gene detection indicates the pathogenicity of the virus, the number of repeat sequences of four prolines (PPPP repeats) in the meq gene (overall range 2-8) have been reported to correlate with MDV virulence and oncogenicity [19] with the most pathogenic isolates having the fewest number of repeats [17]. Compared with 30 reference strains, both the isolates have 5 PPPP repeats similar to the six isolates from north India [9] and one each from Hungary and South India indicating the virulence potential. The isolates in cluster II have 2-4 PPPP repeats while the isolates in cluster III have PPPP repeats ranges from 4 to 7 probably indicating the level of pathogenic potential of the isolates in each clusters.…”
Section: Phylogenetic Analysis and Determination For Virulencementioning
confidence: 98%
“…At the moment in vivo studies are mandatory for an accurate inclusion of GaHV‐2 strains into one of the known pathotypes. The meq gene polymorphism is also useful to create epidemiological molecular linkages between various GaHV‐2 strains, according to the numerous studies that have been recently published from various countries: China (Tian et al, ; Yu et al, ; Zhang, Liu, Zhang, Shi, & Li, ), Poland (Woźniakowski & Samorek‐Salamonowicz, ), USA (Padhi & Parcell, ), Colombia (Lòpez‐Osorio et al, ), Egypt (Abdallah et al, ; Hassanin, Abdallah, & El‐Araby, ), India (Gupta, Deka, & Ramneek, ; Prathibha, Sreedevi, Vinod Kumar, & Srilatha, ; Suresh, Johnson Rajeswar, Sukumar, Harikrishnan, & Srinivasan, ) and Japan (Abd‐Ellatieff et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This data revealed that seven Meq amino acid sequences of Ludhiana isolates had the highest sequence similarity with LSY (LN07I), LCD (SC07II), CVI 988/Rispens vaccine strain and mCU-2 strain. The values of similarity between the sequences are reported in [1] .…”
Section: Datamentioning
confidence: 99%